Online Exam in Electronic Learning Design - Betria, Tigus Juni; Hapsarib, Alfonsa Maria Sofia (International Journal of Psychosocial Rehabilitation, 2020)
Digital Revolution 4 requires all educational institutions to adjust to the changing times. At present electronic learning is the first demand in all educational institutions. Not only in the scope of the University even in the scope of high schools and junior high schools are required to apply this technology. E-Learning, previously known as a medium for teaching and learning activities, is now beginning to rise to the exam model. The online exam model is expected to be applied in educational institutions start from Middle School, besides adjusting to the changing times, as well as a media to familiarize students with electronic-based examinations. So that when they go to college or into their time to work, students are not surprised by what they face. For example college entrance test or CPNS(civil servant) entrance test which are now using the online examination system or commonly called CAT (Computer Assisted Test). Design Structured programming is needed in the application design stage, including system design, database design, interface design, and prototype. With the application of the online exam tool, it is expected that students in middel school environments can improve their competency in using information technology.